A study on the relationship between student' learning engagements and higher-order thinking skills in programming learning - Li, Wei; Huang, Ji-Yi; Liu, Cheng-Ye; Tseng, Judy C.R.; Wang, Shu-Pan (Thinking skills and creativity, 2023)
•Higher-order thinking skills are essential competencies for the 21st century.•Programming education improves higher-order thinking skills effectively.•The impact of learning engagement on higher-order thinking skills is multi-dimensional.•Learning engagements are critical factors in developing higher-order thinking skills. Learning engagements in programming learning activities are critical to developing students' higher-order thinking skills. This study aimed to investigate the relationship between K-12 students' learning engagement levels (i.e., cognitive engagement, emotional engagement, and behavioral engagement) and higher-order thinking skills (i.e., computational thinking, problem solving, creative thinking, and critical thinking) in programming learning, and the moderating effects of behavioral engagement and emotional engagement on this relationship. A total of 714 K-12 students in China's Zhejiang Province participated in this study and completed an online questionnaire, which included the learning engagement scale and the high-order thinking tendency scale. Cross-sectional survey data were analyzed using Pearson's correlation coefficient and hierarchical multiple regression as a way to examine the relationship between the variables. The results showed that cognitive engagement, emotional engagement, and behavioral engagement were all key factors in developing those students' higher-order thinking for programming learning activities in K-12 students during associated activities. Furthermore, when the students' emotional engagements were elevated, the positive relationships between cognitive engagement, computational thinking, and creative thinking were closer. Inversely, when students' behavioral engagement was high, the positive relationship between cognitive engagement and critical thinking, and the positive relationship between emotional engagement and problem-solving and critical thinking became looser. These results can help deepen educators' understanding of the relationship between learning engagement and higher-order thinking skills to facilitate their search for effective strategies to improve programming instruction. Additionally, it can provide a more precise research direction for the broader development of programming education.